Memory-driven capture occurs for individual features of an object - Sasin, Edyta (Sci Rep, 2020)
Items held in working memory (WM) capture attention (memory-driven capture). People can selectively prioritize specific object features in WM. Here, we examined whether feature-specific prioritization within WM modulates memory-driven capture. In Experiment 1, after remembering the color and orientation of a triangle, participants were instructed, via retro-cue, whether the color, the orientation, or both features were relevant. To measure capture, we asked participants to execute a subsequent search task, and we compared performance in displays that did and did not contain the memory-matching feature. Color attracted attention only when it was relevant. No capture by orientation was found. In Experiment 2, we presented the retro-cue at one of the four locations of the search display to direct attention to specific objects. We found capture by color and this capture was larger when it was indicated as relevant. Crucially, orientation also attracted attention, but only when it was relevant. These findings provide evidence for reciprocal interaction between internal prioritization and external attention on the features level. Specifically, internal feature-specific prioritization modulates memory-driven capture but this capture also depends on the salience of the features.